2020
DOI: 10.3389/fmars.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Perception of Climate Change by Representatives of Public Authorities and Designing Coastal Climate Services: Lessons Learnt From French Polynesia

Abstract: Institutional actors have a crucial role in adaptation to climate change, especially for highly vulnerable territories such as small tropical islands. Here, we emphasize their major role in the co-design of tailored coastal climate services (CCS) based on a case study of French Polynesia. In this perspective, we assessed climate change perceptions by public authorities and identified their needs with regard to climate-related science. This assessment included an analysis of the decision-making context, semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Some scholars analyzed the adaptation behaviors and influencing factors of peasants in the hilly loess regions of northern Shaanxi and concluded that peasants' adaptation behaviors are affected by the perception of climate change (Figure 7). In addition [51], family socioeconomic attributes have a significant impact on the probability of peasants' adaptation behaviors, while other attributes such as age and education level are independent of the probability of farmers adopting adaptive behaviors [52] (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars analyzed the adaptation behaviors and influencing factors of peasants in the hilly loess regions of northern Shaanxi and concluded that peasants' adaptation behaviors are affected by the perception of climate change (Figure 7). In addition [51], family socioeconomic attributes have a significant impact on the probability of peasants' adaptation behaviors, while other attributes such as age and education level are independent of the probability of farmers adopting adaptive behaviors [52] (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies have shown that relocation might be accepted, but usually with longer time scales (Minéo-Kleiner, 2017;Rey-Valette et al, 2019). This sense of urgency for implementing adaptation solutions in Miquelon, and in Saint-Pierre-and-Miquelon more generally, is uncommon: other studies highlight that the economic situation, pollution or waste problems are more likely to be seen as urgent issues, especially in island communities (Terorotua et al, 2020). In Saint-Pierre-and-Miquelon, this sense of urgency for adaptation may indicate both a sudden awareness of the risks and a wish to preserve the territory, due to strong place attachment.…”
Section: Social Acceptance Of Adaptation Depends On Place Attachment Experience Of Natural Hazards and Socio-demographic Characteristicsmentioning
confidence: 99%
“…Past studies on disaster responses examined risk perceptions of local government officials to understand local institutional capacity [10][11][12]. Local actors' awareness of disaster responses and displacement challenges play a critical role in preparing for evacuation and making evacuation decisions for those in vulnerable areas [13].…”
Section: Introductionmentioning
confidence: 99%